Constructivist Approach to Learning based on the Concepts of Jean Piaget and Lev Vygotsky An Analytical Overview - Devi, Koijam Sobita (JOURNAL OF INDIAN EDUCATION, 2019)
The goal of learning is not to store piles of information but to engage children’s minds by constructing powerful and useful concepts. The behaviorist approach to learning focuses only on the behaviour that can be externally observed without considering the influence of the unconscious mind. The constructivist approach to learning can facilitate individuals by providing meaningful and relevant information, by giving opportunities to discover or apply ideas themselves and by teaching them to be aware of and consciously use their own strategies for learning. Here, the learners must be capable of discovering basic skills and knowledge to solve complex problems or transform complex information into convenient and suitable information. Jean Piaget viewed children as discovering or constructing virtually all knowledge about their world based on their cognitive levels. According to Vygotsky, the sociocultural context also profoundly affects children’s learning. This paper discusses the different strategies and methods for facilitating constructive learning with broad emphasis on the views of Jean Piaget and Lev Vygotsky.